2008
DOI: 10.1089/neu.2007.0468
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from a Spinal Cord Injury: Significance of Compensation, Neural Plasticity, and Repair

Abstract: Clinical recovery after a lesion of the central nervous system (CNS) can be attributed to mechanisms of functional compensation, neural plasticity, and/or repair. The relative impact of each of these mechanisms after a human spinal cord injury (SCI) has been explored in a prospective European multi-center study in 460 acute traumatic SCI subjects. Functional (activities of daily living and ambulatory capacity), neurological (sensory-motor deficits), and spinal conductivity (motor- and somato-sensory evoked pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
219
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(231 citation statements)
references
References 39 publications
6
219
3
3
Order By: Relevance
“…84 In a longitudinal study, persons with motorincomplete SCI demonstrated increased amplitude of motor evoked potentials over the course of the first post-injury year (with no associated change in latency). 85 While the sample sizes in some subgroups were too small to reach statistical significance, the mean change in motor evoked potentials suggests a parallel between cortical connectivity and motor scores.…”
Section: Training-related Modulation Of Supraspinal Circuitsmentioning
confidence: 97%
“…84 In a longitudinal study, persons with motorincomplete SCI demonstrated increased amplitude of motor evoked potentials over the course of the first post-injury year (with no associated change in latency). 85 While the sample sizes in some subgroups were too small to reach statistical significance, the mean change in motor evoked potentials suggests a parallel between cortical connectivity and motor scores.…”
Section: Training-related Modulation Of Supraspinal Circuitsmentioning
confidence: 97%
“…Information collected from international SCI registries, such as the European Multi-center Study about Spinal Cord Injury, has already contributed to large-scale observational studies on topics such as American Spinal Injury Association (ASIA) Impairment Scale (AIS) validation 3 and spontaneous recovery patterns. 4 Other SCI registries such as the US Model SCI Database have contributed greatly to our understanding of the epidemiology of traumatic SCI 5 and predictors of participation and quality of life following injury. 6 In Canada, the first SCI patient registry known as the Rick Hansen Spinal Cord Injury Registry (RHSCIR) was launched in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…However, Burns et al 9 reported that in chronic subjects, the assessment of maximum WISCI II level by the two examiners differed in two of 63 (3%) cases, with higher reliability coefficients than those reported in our study. Therefore, according to previous studies 18,19 that state that measurement errors, and thus the reliability of a measure, are not a fixed property but are dependent on the studied population, in the effort of improving the generalizability of the WISCI II, we decided to enlarge our pilot study on acute SCI patients.The rationale for examining the highest WISCI II level has been presented by several studies of chronic patients. 8,9,20 Reliability and responsiveness The reliability of the WISCI was established in its development when a videotape of patients who were walking at each level (40 randomized clips) was circulated to SCI experts.…”
mentioning
confidence: 99%